The Origins of Modern Welfare Juan Luis Vives, "De Subventione Pauperum", and City of Ypres, "Forma Subventionis Pauperum" - Spicker, Paul; Spicker, Paul (Peter Lang, 2011)
This book presents new translations of the earliest known studies in Social Policy. Juan-Luis Vives$1 (Bs De Subventione Pauperum (On the Relief of the Poor) is an academic report on the organisation of social welfare, prepared for the senate of Bruges and published in 1526. Forma Subventionis Pauperum (The government of poor relief), published in 1531, is an anonymous evaluation report. It reviews the system of poor relief in the city of Ypres, five years after the policy was introduced. These reports lay out methods and approaches for the delivery of social services within their cities. Unemployed people should be found work or helped to start a business. People with disabilities or mental illness should be treated seriously and recognised for what they can do. Migrants should be helped, even if it is not possible to assist everyone. Special efforts should be made to help people who are reluctant or too proud to claim. Services have to be properly organised, records have to be kept and the use of funds has to be publicly accountable and subject to audit. The sophistication of the arguments developed in these studies will surprise many readers. They deserve to be read by everyone with an interest in social policy or public administration.s